A novel pseudotype derived of the canine distemper virus for adapter-mediated lentiviral transduction in vivo - Nora Winter; Carolin Kolbe; Shima Ferdos; Larissa Steiner; Nils Bartelsen; Dominik Lock; Fabian Engert; Boris Engels; Mario Assenmacher; Michael Schindler; Ulrich M. Lauer; Thomas Schaser; et al. (Molecular Therapy: Methods & Clinical Development)
Targeted cell entry with lentiviral vectors (LVs) is one approach to enable efficient and specific gene delivery in the context of immunotherapies, such as chimeric antigen receptor (CAR)-T cell therapy. We have recently shown the generation of CAR-T products with varying CD4:CD8 ratios with our selective, universal Adapter-LV system. However, low viral vector titers limit the clinical and in vivo applications of our measles virus (MV)-based system. Here, we report a novel pseudotype based on canine distemper virus (CDV) for the Adapter-LV system (CDV-Ad-LV) and show improved viral vector yield while maintaining flexibility, selectivity, and transduction efficacy. As for MV, the engineered CDV envelope protein is fused to a single-chain variable fragment that binds biotin in the context of a defined chemical linker. Thereby, Adapter-LVs bind only to biotinylated adapter molecules, which in turn bind the antigen of choice. Besides extensive characterization in vitro, we evaluated transduction in vivo with CDV-Ad-LVs and showed high transduction efficiencies of CD4+ and CD8+ T cells following a single-dose injection into human PBMC-transplanted immunodeficient non-obese diabetic (NOD) SCID gamma (NSG) mice. Hence, CDV-Ad-LVs represent a novel and efficient system for adapter-mediated transduction, which broadens the potential of the Adapter-LV technology, going beyond CAR-T cell therapy applications.